2010
DOI: 10.1258/phleb.2009.009001
|View full text |Cite
|
Sign up to set email alerts
|

Outcome following saphenopopliteal surgery: a prospective observational study

Abstract: This study demonstrates that preoperative duplex SPJ marking results in a high percentage of successful ligation. Given that residual persistent reflux was avoided in patients who underwent stripping of the SSV, we propose that patients who require SPJ surgery undergo duplex marking along with specific consideration with regard to treatment of the residual SSV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Our study, similar to results reported by Ikponmwosa et al , 19 clearly demonstrated the usefulness of preoperative duplex marking which facilitated in positively identifying the SPJ in all 50 limbs. This is in stark contrast to some of the studies that have reported no better outcomes with preoperative duplex marking.…”
Section: Discussionsupporting
confidence: 92%
“…Our study, similar to results reported by Ikponmwosa et al , 19 clearly demonstrated the usefulness of preoperative duplex marking which facilitated in positively identifying the SPJ in all 50 limbs. This is in stark contrast to some of the studies that have reported no better outcomes with preoperative duplex marking.…”
Section: Discussionsupporting
confidence: 92%
“…A more recent study by Ikponmwosa et al looked at the role of adjunctive pre-operative duplex skin marking given the anatomical variability of the SPJ. 30 In a total of 90 limbs, the authors found that the SPJ was successfully ligated in 87 (96.7%) cases. Reflux was completely abolished in 51 (56.7%) cases but persisted solely in the small saphenous vein (SSV) in 32.2%.…”
Section: Small Saphenous Vein Surgerymentioning
confidence: 97%
“…A similar approach is recommended for the lesser saphenous vein with its anatomically quite variable junction, where again ligation should be performed as close as possible to the junction [4]. At the moment it is still unclear if the interruption of muscle veins at the saphenopopliteal junction is indicated and contributes to the prevention of recurrences.…”
Section: Classical Varicose Vein Surgerymentioning
confidence: 99%